Urgensi Pendidikan Kewarganegaraan Sebagai Upaya Mewujudkan Demokrasi Konstitusional dan Konstitusionalisme di Indonesia - Daulat Nathanael Banjarnahor; Firinta Togatorop (Departement of Mathematics Education, 2023)
Contextually, one of the essences of the ideology and constitution of Indonesia is the existence of democracy within the state system. Then in its development in Indonesia understand the system of constitutional democracy and understand the understanding of constitutionalism in the state. However, at this time constitutional democracy and the notion of constitutionalism adopted by Indonesia are stated by many parties to have not run well, and have problems. Based on the results of the LP3ES survey, democracy in Indonesia is declared to be in decline, with a total of 31 (thirty one) problems in the implementation of democracy in Indonesia, some of which are money politics in general elections, populism and identity politics, political corruption. The research method used in answering the problems in this scientific writing is a Descriptive Qualitative Method with a Phenomenological Research Approach. The technique of collecting data in the preparation of this article is carried out by searching and various data from online search engines in the form of publications of scientific journals, government circulars, newspapers, and other website services that actively discuss topics related to Citizenship Education by realizing constitutional democracy and constitutionalism. in Indonesia. the urgency of civic education to build constitutional democracy and constitutionalism because: first, there is an increasing tendency to be politically illiterate, and citizens do not know how democracy and its institutions work. Second, political apathy which has also increased with the indicator that few citizens are involved in political activities. In this case civics education can play a role as a seed for the constitution of democracy and constitutionalism